المسؤولية الاجتماعية للشركات ((CSR في المصارف من وجهة نظر العملاء دراسة ميدانية في اللاذقية - غدير, باسم; دغمان, لبنى (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The present study aimed to explore the relationship between each of the knowledge of the customers and the importance of corporate social responsibility for them as well as personal characteristics as independent variables, and between their perceptions of the level applied in banks that are dealing with it as the dependent variable. Through soft sample of public and private banking customers in Latakia province reached, numbering 200, were distributed to them questionnaires included 18 questions about the independent variables mentioned and dependent variable. Researchers have been able to recover 115 questionnaires, 105 of which was only capable of statistical analysis using SPSS software. The study concluded that there is a direct positive relationship between each of the importance, knowledge, and customers' personal characteristics, and between their perceptions about CSR in their banks. But with little effect on those factors, personal perceptions. The study recommended that banks apply to programs of social responsibility in Latakia province, contribute to the deployment of banking culture and serve the benefit of customers and market banks' image well. تهدف الدراسة إلى استكشاف العلاقة بين كل من معرفة العملاء بالمسؤولية للشركات وأهميتها بالنسبة لهم وكذلك خصائصهم الشخصية كمتغيرات مستقلة، وبين تصوراتهم لمستوى تطبيقها في المصارف التي يتعاملون معها كمتغير تابع. من خلال عينة ميسرة من عملاء المصارف العامة والخاصة في مدينة اللاذقية بلغ تعداد أفرادها 200، وزعت لهم استبيانات تضمنت 18 سؤالاً حول المتغيرات المستقلة المذكورة والمتغير التابع. وقد تمكن الباحثون من استرداد 115 استبيان، كان 105 منها فقط قابلاً للتحليل الإحصائي باستخدام برنامج SPSS. وقد خلصت الدراسة إلى وجود علاقة إيجابية طردية بين كلّ من المعرفة والأهمية والخصائص الشخصية للعملاء وبين تصوراتهم حول CSR في مصارفهم. لكن مع وجود تأثير ضئيل للعوامل الشخصية على تلك التصورات. وقد أوصت الدراسة بضرورة تطبيق المصارف لبرامج مسؤولية اجتماعية في مدينة اللاذقية تسهم في نشر الثقافة المصرفية وإفادة العملاء وتسويق المصارف بصورة جيدة.